Application of Failure Mode, Effect Analysis (FMEA) and Ishikawa Diagram in Determining the Damage Aspects and Maintenance Plan of Screw Feeder of Steam Power Plant Company - Riszal, Akhmad; Yohanes, Eko; Risano, A Yudi Eka; Ibrahim, Fauzi; Saputra, Rizal Adi (Journal of Applied Science, Engineering and Technology, 2025)
The screw feeder is a commonly used material transporter in various industries due to its ability to move large quantities of material and operate for extended periods. In practice, unexpected damage often occurs, requiring component replacements outside regular maintenance schedules. To improve reliability, Ishikawa diagrams are used to identify root causes of damage, while the FMEA method helps analyze failure risks and schedule preventive maintenance. This study found that the main causes of screw coal feeder damage are human error, mechanical issues, materials, and methods. Recommended actions include regular inspections for wear and proper lubrication to maintain performance. Based on reliability analysis, the screw feeder leaf has a reliability rate of 95.3% with a mean time between failure (MTBF) of 116.66 hours. The casing has a reliability rate of 94.6% and an MTBF of 142.85 hours. Implementing Ishikawa and FMEA methods at PT XYZ’s coal-fired power plant (PLTU) enables more effective and planned maintenance. This approach minimizes unexpected breakdowns, improves component reliability, and ensures smoother operations.